1997
DOI: 10.1093/mnras/292.2.419
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of cooling flows and general cluster properties from an X-ray image deprojection analysis of 207 clusters of galaxies

Abstract: In this paper we present an X-ray image deprojection analysis of EINSTEIN OBSERVATORY imaging data on 207 clusters of galaxies. The resulting radial profiles for luminosity, temperature, and electron density variations are determined from the cluster surface-brightness profiles according to gravitational potential constraints from average X-ray temperatures and optical velocity dispersions. This enables us to determine cooling-flow and other cluster properties, such as baryon fractions, Sunyaev-Zeldovich micro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
517
4
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 411 publications
(569 citation statements)
references
References 44 publications
47
517
4
1
Order By: Relevance
“…For most of the clusters considered here, X-ray imaging is not available, so that we cannot assess whether they host a cool core or not. Only two of our galaxies have been confirmed to be hosted by a non-cooling flow cluster (White et al 1997) and for those we find contradictory results: 2001 is one of the oldest galaxies in our sample, consistent with the cool core hypotheses, however, 1066 shows a young central region and a positive age gradient, suggesting that cool cores are not the explanation for the intermediate ages observed.…”
Section: Stellar Agessupporting
confidence: 37%
“…For most of the clusters considered here, X-ray imaging is not available, so that we cannot assess whether they host a cool core or not. Only two of our galaxies have been confirmed to be hosted by a non-cooling flow cluster (White et al 1997) and for those we find contradictory results: 2001 is one of the oldest galaxies in our sample, consistent with the cool core hypotheses, however, 1066 shows a young central region and a positive age gradient, suggesting that cool cores are not the explanation for the intermediate ages observed.…”
Section: Stellar Agessupporting
confidence: 37%
“…This relation has been shown by several independent analyses to have a slope, L X ∝ T α , with α 3 for T 2 keV (e.g., White et al 1997), with indications for a flattening to α 2.5 for the most massive systems (Allen and Fabian 1998). The scatter in this relation is largely contributed by the cool-core emission, so that it significantly decreases when excising the cores (Markevitch 1998) or removing cool-core systems (Arnaud and Evrard 1999).…”
Section: The Luminosity-temperature Relationmentioning
confidence: 72%
“…If the density of gas outside the core is greater in cooling-Ñow clusters than in nonÈcooling-Ñow clusters, more metals will be released into the gas phase for the former. A di †erence in density among cooling and nonÈ cooling-Ñow clusters outside of 200 kpc was observed by White et al (1997), who deprojected the surface-brightness proÐles of 207 clusters observed with Einstein Observatory and found that the electron densities of clusters with cooling rates greater than 10 yr~1 were larger than for clusters M _ with cooling rates less than 10 yr~1 out to a radius of 1 M _ Mpc. For a 7 keV cluster, our bin corre-0.075È0.173r virial sponds to 240È560 kpc.…”
Section: Cooling-versus Nonècooling-ñow Clustersmentioning
confidence: 90%
“…For a 7 keV cluster, our bin corre-0.075È0.173r virial sponds to 240È560 kpc. At a radius of 450 kpc, White et al (1997) found that the cooling-Ñow clusters had an electron density of D7 ] 10~4 cm~3, whereas the nonÈcooling-Ñow clusters had an electron density of D3 ] 10~4 cm~3. For a grain lifetime of yr (where a is the size of the (2 ] 106)a/n e grain in microns and is the electron density of the hot gas n e in cm~3), grains with a size of around 2 km would survive in nonÈcooling-Ñow clusters for a Hubble time while being sputtered in cooling-Ñow clusters.…”
Section: Cooling-versus Nonècooling-ñow Clustersmentioning
confidence: 99%